Supramolecular Controlled Water Uptake of Macroscopic Materials by a Cyclodextrin‐Induced Hydrophobic‐to‐Hydrophilic Transition. Issue 34 (2nd July 2013) - Peters, Oliver; Ritter, Helmut
<x xml:space="preserve">Abstract</x> A swell memory: Samples of adamantyl‐modified cross‐linked hydrophilic polymers were swollen in water or aqueous cyclodextrin solution. The cyclodextrin dramatically enhanced the swelling (see picture). If the materials were twisted after heating above their glass‐transition temperature and swollen in aqueous cyclodextrin solution, a shape‐memory effect was observed.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>